2022
DOI: 10.1155/2022/1041688
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Vibration Training on Weight Loss and Heart Rate Variability in the Obese Female College Students

Abstract: Objective. The present study examined the effects of a 12-week whole-body vibration training (WBVT) regimen on heart rate variability (HRV) and body composition in the obese female college students. Methods. Participants were assigned to either the WBVT ( n = 17 ) or obese control group ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In only 10 WBV interventions we observed a slight improvement in body composition, as reported in previous studies [28,29]. However, body weight and BMI hardly changed (reduction of 0.6% and 0.5%, respectively), as observed by Deng [30] in a study conducted in China with 39 obese university students. However, Zago et al [28] state that even a modest weight loss (5-10% of body weight) helps reduce cardiovascular risk.…”
Section: Discussionsupporting
confidence: 84%
“…In only 10 WBV interventions we observed a slight improvement in body composition, as reported in previous studies [28,29]. However, body weight and BMI hardly changed (reduction of 0.6% and 0.5%, respectively), as observed by Deng [30] in a study conducted in China with 39 obese university students. However, Zago et al [28] state that even a modest weight loss (5-10% of body weight) helps reduce cardiovascular risk.…”
Section: Discussionsupporting
confidence: 84%
“…Pérez-Gómez et al demonstrated improvements in body fat mass following a WBVE protocol in postmenopausal women [26]. Wei Deng also examined the effects of a WBVE training regimen on obese college students and observed a reduction in body fat percentage [27].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%